Diversity and Plant Growth-Promoting Properties of Rhodiola rosea Root Endophytic Bacteria - Inga Tamošiūnė; Muhammad Fahad Hakim; Odeta Buzaitė; Vidmantas Stanys; Jurgita Vinskienė; Elena Andriūnaitė; Danas Baniulis (Microorganisms)
Plants inhabiting environments with suboptimal growth conditions often have a more pronounced capacity to attract and sustain microbial communities that improve nutrient absorption and expand abiotic stress tolerance. Rhodiola rosea L. is a succulent plant of the Crassulaceae family adapted to survive in sandy or rocky soils or dry tundra. The aim of the present study was to investigate the diversity and plant growth-stimulating potential of R. rosea endophytic microbiota. Metataxonomic analysis of the bacterial diversity in the rhizome of R. rosea revealed 108 families. Among these, three families were found exclusively in the core microbiome of 1-year-old plants, while nine families were unique to the core microbiome of mature plants grown in the field for more than 4 years. Seventy-three endophytic bacteria isolates were obtained from the rhizome of R. rosea plants and were assigned into 14 distinct bacterial genera of Firmicutes (26%) or Proteobacteria (74%) phyla. Screening for functional genes related to the nitrogen cycle, phosphorus mineralisation or dissolution, and traits associated with nitrogen fixation (56% of isolates), siderophore production (40%), inorganic phosphorus solubilisation (30%), and production of indole-related compounds (51%) led to the classification of the isolates into 16 distinct clusters. Co-cultivation of 45 selected isolates with germinating Arabidopsis seedlings revealed 18 and 5 isolates that resulted in more than a 20% increase in root or shoot growth, respectively. The study results established the complexity of the succulent R. rosea endophytic microbiome and identified isolates for potential plant growth-stimulating applications.